Synthesis of new benzisoxazole derivatives and their antimicrobial, antioxidant and anti-inflammatory activities - Shivaprasad, Chalya Mallappaji; Jagadish, Swamy; Swaroop, Toreshettahally Ramesh; Mohan, Chakrabhavi Dhananjaya; Roopashree, Rangaswamy; Kumar, Kothanahally Shivaramu Sharath; Rangappa, Kanchugarakoppal Subbegowda (European Journal of Chemistry, 2014)
A series of benzisoxazole derivatives were synthesized and evaluated for their antibacterial, antioxidant and anti-inflammatory activities. The results indicated that most of the compounds exhibit moderate antimicrobial activity against Gram negative (Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Shigella flexineri) and Gram positive (Bacillus subtilis) bacterial culture. The molecules were evaluated for antioxidant activities using 2,2-diphenyl-1-picrylhydrazyl scavenging, super oxide radical scavenging and hydroxyl radical scavenging assays and most of them showed good antioxidant activities. Also, the synthesized compounds were screened for anti-inflammatory activities such as lipoxygenase inhibition and indirect haemolytic assays.